2021
DOI: 10.3390/plants10030519
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Proteotoxic Stress Responses Triggered by the Perturbed Thylakoid Proteostasis in Arabidopsis

Abstract: Here, we explored heat dependent thylakoid FtsH protease substrates and investigated proteotoxicity induced by thermal damage and processive protease dysfunction on the thylakoid membrane. Through our thylakoid enriched proteome analysis and biochemical experiments, carbonylated stromal proteins were suggested as possible FtsH targets. Furthermore, we observed in the thylakoid fractions in the absence of FtsH stromal reactive oxygen species-detoxifying enzymes, as well as heat shock proteins and chaperones, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
(71 reference statements)
0
2
0
Order By: Relevance
“…OsGSTL2 transgenic rice improves glyphosate and chlorsulfuron tolerance [55]. OsGSTL3 confers quizalofop-p-ethyl resistance to Polypogon fugax [58] Herein, it was observed that there was a differential profile in the expression of OsGSTL3 as a product of temperature changes over time, probably by its role as ROS scavenger [59]. However, it cannot be proven if the FPB spraying caused an overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…OsGSTL2 transgenic rice improves glyphosate and chlorsulfuron tolerance [55]. OsGSTL3 confers quizalofop-p-ethyl resistance to Polypogon fugax [58] Herein, it was observed that there was a differential profile in the expression of OsGSTL3 as a product of temperature changes over time, probably by its role as ROS scavenger [59]. However, it cannot be proven if the FPB spraying caused an overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with this hypothesis, proteome analysis of chloroplast thylakoid fractions depleted of the FTSH protease under heat stress identified several extraplastidial cytosolic proteins. However, it is unclear how cytosolic proteins found in thylakoid fractions of heat-treated plants lacking FTSH could be relocated into the chloroplast [ 72 ]. Future efforts must be made to unveil if chloroplasts are capable of importing misfolded cytosolic proteins for further degradation.…”
Section: Future Research Directions In Chloroplasts Proteostasismentioning
confidence: 99%